1995
DOI: 10.1089/lps.1995.5.101
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laparoscopic Surgery in the Management of Acute Abdomen in the HIV-Positive Patients

Abstract: Emergency open laparotomy in patients infected with HIV is accompanied by high mortality. The authors investigated the potential role of a laparoscopic approach for the management of acute abdomen in such patients. Prospectively, 10 patients with HIV disease (9 with AIDS) underwent laparoscopy for acute abdomen. The treatment was exclusively laparoscopic in 6 patients. A conversion to laparotomy was necessary in 4 patients but through guided elective incision in 3 of them. The postoperative course was uneventf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Finally, two possible additional advantages of the laparoscopic approach are the reduced immunosuppression observed in response to the surgical trauma, and recently, Fry [15] reported a reduced risk of transmission of viral infections such as HIV in surgeons and medical personnel [13], a point also made by Bouillot et al [2]. On the other hand, although the expulsion of live particles during the evacuation of pneumoperitoneum has been shown, to this date there is no evidence that HIV can be transmitted in this way [2,3]. We recommend evacuating the smoke and pneumoperitoneum with a suctionirrigation system.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two possible additional advantages of the laparoscopic approach are the reduced immunosuppression observed in response to the surgical trauma, and recently, Fry [15] reported a reduced risk of transmission of viral infections such as HIV in surgeons and medical personnel [13], a point also made by Bouillot et al [2]. On the other hand, although the expulsion of live particles during the evacuation of pneumoperitoneum has been shown, to this date there is no evidence that HIV can be transmitted in this way [2,3]. We recommend evacuating the smoke and pneumoperitoneum with a suctionirrigation system.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a higher rate of morbidity and mortality in urgent appendectomies for acute appendicitis in patients with acquired immunodeficiency syndrome (AIDS) because of the diagnosis and surgical management delay, the surgeon's worry of opportunistic infections, and weakened immune responses. 2,[6][7][8] Although one study has demonstrated the benefits of laparoscopic appendectomy (LA) 9 in HIV-infected patients, no study has compared LA versus open appendectomy (OA) in AIDS patients. This study is the largest nationwide study available for appendicitis in patients with AIDS.…”
mentioning
confidence: 99%
“…In the AIDS patient it can be used to evaluate and treat both specific and nonspecific clinical presentations [2,12]. The surgeon can obtain fluid for cytology and culture and tissue for inspection.…”
Section: Resultsmentioning
confidence: 99%